Approaches to Measuring the Conservation Impact of Forest Management Certification - Romero, Claudia; Castrén, Tuukka (Program on Forests (PROFOR), Washington, DC, 2014)
Sustainable forest management (SFM) certification emerged in the 1980s and 1990s as a mechanism to promote responsible forest use and as an alternative to boycotts of forest products amid growing concerns about forest degradation and destruction. Since then, forest certification has evolved into a multifaceted market-based mechanism to promote compliance with sets of ecological, social, and economic criteria to enhance sustainability. Commodity certification has evolved from its origins as a means of verifying organic and environmentally sustainable production; issues like social equity, transparency, participation, and legal compliance have become increasingly relevant. One commonality in all certification schemes is that they are voluntary, market-driven ('willing buyer, willing seller') schemes aimed at transformational change toward more sustainable production and consumption patterns within existing market structures. This document presents the state of the current knowledge on how to assess impacts of forest management certification. It also discusses the design, implementation, and use of forest management certification. It focuses on methodologies to provide evidence-based information on the environmental impacts of certification. The concluding chapter briefly discusses the economic and social impacts. The objective is to identify areas where further methodological work is needed to improve understanding on the impacts of certification. Many benefits of certification, like improved information on management practices by outside stakeholders (for example, consumers, governments) are undisputed. At the same time, there is less knowledge on whether or not practices at field level have changed and how much. Although improved information as such is a valuable outcome, more quantitative information on environmental impacts will be welcome.